Concentration of power at the editorial boards of economics journals - Ductor, Lorenzo,Visser, Bauke (Tinbergen Institute, 2021)
Evolutionary arguments and incentive theory point to the importance of variety and rotation of editorial board members to stimulate innovative research. Using a unique dataset covering more than 100 economics journals over the period 1990-2011, we document trends in the incidence of multiple positions, editorial duration and institutional background for more than 6,100 board members. We put these figures into perspective using the literature on boards of directors and measures of market concentration. The picture that emerges is of a discipline with a high concentration of institutional and individual power, especially at the more prestigious journals. Evidence suggests this indeed matters: there is a strong negative association between editorial duration and journal impact.
10419/237777
Keywords: Graue Literatur; editorial boards; journals; concentration; power; busyness; impact